Exploring the lutein therapeutic potential in steatotic liver disease: mechanistic insights and future directions - Balboa, Elisa; Saud, Faride; Parra-Ruiz, Claudia; de la Fuente, Marjorie; Landskron, Glauben; Zanlungo, Silvana (Frontiers in Pharmacology, 2024)
The global prevalence of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) is increasing, now affecting 25-30% of the population worldwide. MASLD, characterized by hepatic steatosis, results from an imbalance in lipid metabolism, leading to oxidative stress, lipoperoxidation, and inflammation. The activation of autophagy, particularly lipophagy, alleviates hepatic steatosis by regulating intracellular lipid levels. Lutein, a carotenoid with antioxidant and anti-inflammatory properties, protects against liver damage, and individuals who consume high amounts of lutein have a lower risk of developing MASLD. Evidence suggests that lutein could modulate autophagy-related signaling pathways, such as the transcription factor EB (TFEB). TFEB plays a crucial role in regulating lipid homeostasis by linking autophagy to energy metabolism at the transcriptional level, making TFEB a potential target against MASLD. STARD3, a transmembrane protein that binds and transports cholesterol and sphingosine from lysosomes to the endoplasmic reticulum and mitochondria, has been shown to transport and bind lutein with high affinity. This protein may play a crucial role in the uptake and transport of lutein in the liver, contributing to the decrease in hepatic steatosis and the regulation of oxidative stress and inflammation. This review summarizes current knowledge on the role of lutein in lipophagy, the pathways it is involved in, its relationship with STARD3, and its potential as a pharmacological strategy to treat hepatic steatosis.